2011
DOI: 10.1130/g32016.1
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-dominated ash settling from the Eyjafjallajökull volcanic cloud illuminated by field and laboratory high-speed imaging

Abstract: The recent Eyjafjallajökull (Iceland) eruption strikingly underlined the vulnerability of a globalized society to the atmospheric dispersal of volcanic clouds from even moderate-size eruptions. Ash aggregation controls volcanic clouds dispersal by prematurely removing fi ne particles from the cloud and depositing them more proximally. Physical parameters of ash aggregates have been modeled and derived from ash fallout deposits of past eruptions, yet aggregate sedimentation has eluded direct measurement, limiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 25 publications
9
95
0
Order By: Relevance
“…Both model and satellite retrievals, used as input to the inversion, operate today with assumed equal ash characteristics during the whole eruption period. Other processes, such as fine ash aggregation that increases the gravitational settling speed and reduces the atmospheric residence time (Brown et al, 2011), were also observed during the Eyjafjallajökull eruption (Taddeucci et al, 2011), but are not included in the model at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Both model and satellite retrievals, used as input to the inversion, operate today with assumed equal ash characteristics during the whole eruption period. Other processes, such as fine ash aggregation that increases the gravitational settling speed and reduces the atmospheric residence time (Brown et al, 2011), were also observed during the Eyjafjallajökull eruption (Taddeucci et al, 2011), but are not included in the model at this time.…”
Section: Discussionmentioning
confidence: 99%
“…The timescales of aggregate formation are short: for example, AP1 aggregates were deposited within five minutes of the onset of the 1990 eruption of Sakurajima volcano, Japan (Gilbert and Lane, 1994) In long-lived ash clouds (>1 day), cloud water concentrations fall close to background levels due to mixing and sedimentation (e.g., Schumann et al, 2011), and electrostatic forces may then play an important role in particle binding (James et al, 2003). Aggregation played an important role in the settling of ash from eruption clouds generated during the 2010 eruption of Eyjafjallajökull volcano, Iceland (Taddeucci et al, 2011). Ground observations indicate that in May 2010 fine ash reached the surface as both particle clusters and accretionary pellets (e.g., Fig.…”
Section: Visual Observationsmentioning
confidence: 99%
“…The dirty thunderstorm mechanism requires ice particles in the plume and is only likely to be important for plumes which reach altitudes with temperatures that allow freezing to occur electric potential gradient necessary to generate lightning discharges. Clustering can be particularly effective in the presence of prevalently fine ash-laden jets exiting volcanic conduits 15 thus facilitating ash aggregation in the plume (Taddeucci et al 2011). Further charging by the formation of hydrometeors (i.e.…”
Section: Ice Related Charging (Dirty-thunderstorm)mentioning
confidence: 99%